Ultrasmall PdPtCo trimetallic nanorings with enriched low-coordinated edge sites and optimized compositions for effective oxygen reduction electrocatalysis. Issue 29 (14th July 2021) - Zhen, Chao; Lyu, Zixi; Liu, Kai; Chen, Xuejiao; Sun, Yu; Liao, Xinyan; Xie, Shuifen
Abstract : Ultrasmall two-dimensional Pd55 Pt18 Co27 trimetallic alloy nanorings with enriched low-coordinated edge sites exhibit greatly enhanced ORR electrocatalytic activity. Abstract : Ultrasmall two-dimensional (2D) PdPtCo trimetallic nanorings (NRs) with enriched low-coordinated edge sites were facilely synthesized through a template-directed approach. The resulting Pd55 Pt18 Co27 NRs/C, featured with the highest edge to surface ratio and optimized composition, exhibits obviously enhanced oxygen reduction reaction (ORR) electrocatalytic activity.